Análisis demográfico del comportamiento del consumidor de los servicios bancarios en la ciudad de Machala - Cevallos Armijos, Cinthia Elizabeth (2015)
This research work is aimed at analyzing the behavior of the consumers of financial services through a quantitative research to develop strategies and tools that will enable us to improve service levels and customer care, the methodology used was with a quantitative approach which was developed through the use of surveys. At the present time the majority of the people make use of the financial services either within or outside of the city, this is one of the factors that influence that the entities have been concerned about providing a service that is at the height of their consumers, it is very important to take into account the analysis of the behavior of each of its customers to deliver what they expect from financial institutions, the consumer has become the cornerstone in any company already that thanks to it generates the profitability and mutual benefit. The financial system in our country is strong in the remainder of the year 2015 according to the Superintendence of Popular and Solidarity Economy, this sector is growing leads to increase the economy of the country and its inhabitants in if. Consumers are looking for higher solvency and security in regard to the provision of such services, they expect to receive the treatment they deserve and demand that the service is more streamlined and with the security that is required for both them and consumers as to the financial institution. To finish i would like to have this on record of the recommendations for the financial sector of the city of Machala, study the changes submitted by the consumer to provide a quality service.